THEME IN SHAKESPEARE’S “KING LEAR” - NFN Mustafa (Balai Bahasa Sulawesi Selatan, 2010)
This paper examines concerning an aging pagan king of ancient Briton, seeks to divide his kingdom among his daughters and their suitors according to a test of how well they can express their love in words. The aim of this paper is to examine theme in Shakespeare’s